USE OF MODERN INFORMATION TECHNOLOGIES IN TEACHING MATHEMATICS - M.Berdibaev; Yuldashev Murodjon Komiljonovich (Galaxy International Interdisciplinary Research Journal, 2021)
This article presents scientific views on the importance of information technology in mathematics. Scientific opinions are concluded based on facts.